2021
DOI: 10.3389/fcomp.2021.682982
|View full text |Cite
|
Sign up to set email alerts
|

‘Alexa, I feel for you!’ Observers’ Empathetic Reactions towards a Conversational Agent

Abstract: Conversational agents and smart speakers have grown in popularity offering a variety of options for use, which are available through intuitive speech operation. In contrast to the standard dyad of a single user and a device, voice-controlled operations can be observed by further attendees resulting in new, more social usage scenarios. Referring to the concept of ‘media equation’ and to research on the idea of ‘computers as social actors,’ which describes the potential of technology to trigger emotional reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This preference among Chinese users aligns with their cultural inclination to anthropomorphize technology [21,38]. Verbal communication encompasses more than mere words; it includes rich, human-like nuances and emotional cues, making these interfaces feel warmer [10,24,71]. Previous HCI studies have shown that text communication is often seen as less natural and warm compared to oral communication [78], which can lead to a reduced sense of anthropomorphism.…”
Section: The Role and Interplay Of Culture And Technology In Shaping ...mentioning
confidence: 84%
“…This preference among Chinese users aligns with their cultural inclination to anthropomorphize technology [21,38]. Verbal communication encompasses more than mere words; it includes rich, human-like nuances and emotional cues, making these interfaces feel warmer [10,24,71]. Previous HCI studies have shown that text communication is often seen as less natural and warm compared to oral communication [78], which can lead to a reduced sense of anthropomorphism.…”
Section: The Role and Interplay Of Culture And Technology In Shaping ...mentioning
confidence: 84%
“…This initial step towards autonomous shopping has the potential to significantly reduce (or even eliminate) the need for human decision-making (de Bellis & Johar, 2020). Social and relational capabilities in VAs may further increase their influence on consumer behavior contributions to such trends (Canziani & MacSween, 2021;Carolus et al, 2021).…”
Section: /48mentioning
confidence: 99%
“…We demonstrate that research on human-VA interaction that ignores the effect of empathy and its social-emotional determinants on future behavioral intentions is likely to generate biased results. The study of humans' empathetic reactions toward social bots mainly aims at developing better empathic agents (Carolus et al, 2021). Following a different approach, this research simulates an agent's empathic behavior to foster a consumer's affective response towards that empathic agent (von der Pütten et al, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Similarly, virtual agents and social robots were shown to elicit social responses (for an overview: Krämer et al, 2015). Studies focused on intelligent voice assistants as devices added the new feature of speech to CASA research (Carolus et al, 2021). Although there were early attempts to analyze the effects of "talking devices" (Nass et al, 1997), implementation of the speech functions was rather poor (desktop computers "talking" with pre-recorded human voices) and of low external validity as devices used at that time simply did not have these features.…”
Section: Media Equation: Media Equals Real Lifementioning
confidence: 99%